Muslim expansion and Byzantine collapse in North Africa - Kaegi, Walter Emil, (Cambridge University Press, 2010)
"Who 'lost' Christian North Africa? Who won it and how? Walter Kaegi takes a fresh look at these perennial questions, with maps and on-site observations, in this exciting new book. Persisting clouds of suspicion and blame overshadowed many Byzantine attempts to defend North Africa, as Byzantines failed to meet the multiple challenges from different directions which ultimately overwhelmed them. While the Muslims forcefully and permanently turned Byzantine internal dynastic and religious problems and military unrest to their advantage, they brought their own strengths to a dynamic process that would take a long time to complete - the transformation of North Africa. An impartial comparative framework helps to sort through identity politics, 'Orientalism' charges and counter-charges, and institutional controversies ; this book also includes a new study of the decisive battle of Sbeitla in 647, helping readers to understand what befell Byzantium, and indeed empires from Rome to the present"--